Forest policy, economics, and markets in Zambia - Ng'Andwe, Phillimon; Mwitwa, Jacob; Muimba-Kankolongo, Ambayeba; Banda, Mathew K. (Elsevier, 2015)
This book is the result of over ten years of field research across Zambia. It covers the production and diverse uses of wood and non-wood forest products in different parts of Zambia. Although a short format, it is a multi-contributed work. It starts an overview of the forestry sector, and covers more specific areas like production, markets and trade of wood and non-wood products; the role of non-wood forest products in the livelihood of the local population, the contribution of the forestry sector to Zambia's overall economy and reviews of efforts to strategically utilize these resources for local economic, and sustainable, development. A concise reference to understand key wood products, market dynamics, and role of forests in a developing nation A useful guide for corporations, consultants, NGOs and international research organizations involved with sustainable development in Zambia as well as other nations in the SADC.